Headgate To Tailgate Cutting Lowers Longwall Shearer Operators' Dust Exposure - Objective (The National Institute for Occupational Safety and Health (NIOSH), 1984)
Reduce dust exposure of longwall shearer operators by keeping them upwind of the primary cutting drum. Approach Use a different coal cutting sequence by cutting from headgate-to-tailgate, making the cleanup pass from tail-gate-to-headgate. How It Works The cutting action of the shearer drum is usually the primary source of respirable dust at longwall shearer faces. Dust exposure of the shearer operator is deter-mined by his position relative to the lead drum, which is normally in the raised position taking a full sump. On long-wall faces where the cut pass is taken from tail-to-head, against the primary airflow, the shearer operators must remain at their controls, on the return-air-side of the primary dust source, to maintain proper control. A simple method to lower shearer operators' dust exposures is to extract the primary coal from head-to-tail, thus positioning the operators up-wind of the lead cutting drum. The bottom coal is then cut, and the floor cleaned by the trailing drum during the tail-to-head cleanup pass. This sequence places the primary dust source, the cutting action of the shearer drums, on the return-air side of both shearer operators, except when cutting out at the longwall headgate.